A case report of Tapia's syndrome after mastectomy and breast reconstruction under general anesthesia. Issue 22 (June 2018) - Jee, Chan hee; Kim, Hyun Jee; Kwak, Kyung-Hwa
Abstract: Rationale: Tapia's syndrome is a rare and potentially anesthesia-related complication that may cause considerable distress to the patient. Here we describe a case of unilateral Tapia's syndrome in a patient undergoing a skin sparing mastectomy and immediate breast reconstruction which, to the best of our knowledge, has not been reported in the literature. Patient concerns: A 41-years old female underwent right skin sparing total mastectomy and breast reconstruction with latissimus dorsi flap under general anesthesia. On the first postoperative day, she complained left sided tongue deviation, subtle hoarseness and swallowing difficulty. Diagnosis: Tapia's syndrome, a combined paralysis of ipsilateral vocal cord and tongue due to injury to the hypoglossal and recurrent laryngeal nerves, in this case, resulting potentially from head and neck position changes Interventions: The patient was closely observed with the administration of empirical prednisolone 5 mg/day for 3 weeks. Outcomes: One month after the surgery, functions of the tongue and vocal cord were completely resolved. Lessons: Particular attention should be paid to the maintenance of adequate cuff pressure, proper position of endotracheal tube and correct neck positioning, especially when procedures taking a long operation time under endotracheal anesthesia and requiring frequent position changes of the patient's head and neck.